(untitled) (Research, Society and Development, 2021)
Canine otohematoma, also called aural or auricular hematoma, is one of the most frequent pathologies in clinical care, being the most affected lesion in dogs. It is described by the accumulation of serous liquid and blood between the cartilage and the epidermis of the external ear causing discomfort in the animals. The objective of this study was to analyze the epidemiology of atrial hematoma in dogs seen and recorded in the Hospital Veterinário das Faculdades Integradas Aparício Carvalho - FIMCA, in the city of Porto Velho, Rondônia, in the period from January 2017 to November 2018. data were obtained through the registries of all patients seen and diagnosed by otohematomas, using factors that may predispose the presence of this affection, such as race, gender or physical size. A total of 13 dogs were diagnosed with the disease, showing two peaks with the highest occurrence, equivalent to the months of September (2 cases, 15.3%) and December (2 cases, 15.3%) of 2017. Undefined animals obtained higher numbers of affections (9/13, 69.2%) and male dogs prevailed (53.8%, 7/13). Most of the animals presented bilateral otohematoma (11/13; 84.6%). Therefore, in the clinical routine of the veterinary hospital analyzed the canine otohematoma presented a relevant number of occurrences, being more common in animals with no defined breed and males, in which this disease was shown to be a risk factor in medium and large animals. The study showed a greater prevalence of bilateral atrial hematoma and the higher prevalence of cases in the months of September and December 2017.